Legal Sanctions Related To The Consideration Of Judges In Decision Number 1306 / K/Pid-Sus/Phi/2017 - Tarmizi, Tarmizi (Universitas Dharmawangsa, 2022)
The issues raised in this thesis are how the legal consequences for workers without a written work Agreement and the consequences for employers or employers, how the legal protection of workers who receive wages under UMP and how the legal sanctions related to the consideration of judges in Decision No. 1306/K / Pdt.Sus-PHI/2017. The research method used in this study is normative juridical research. Normative legal research is a study of secondary data. The nature of this study is descriptive analysis. Data collection techniques this study was conducted by the method of library research (library research). The legal consequences for workers without a written employment agreement and the consequences for employers or employers are expressed as an indefinite employment agreement (PKWTT) or permanent employees. PKWT that is made unwritten is stated as a work agreement for an indefinite period (PKWTT). Legal protection of workers who receive wages under UMP there are two forms, namely preventive protection and repressive protection. Preventive protection is contained in Article 88 Paragraphs (1) and (2) of Law No. 13 of 2003 concerning manpower. Repressive legal protection, can be seen from the decision of the Supreme Court judges in Decision No. 1306/K / Pdt.Sus-PHI/2017 which stated that it sentenced the defendant to pay severance to the plaintiffs in the amount of Rp29, 235, 300.00 (twenty-nine million two hundred thirty-five thousand three hundred rupiah), as a fulfillment of the plaintiff's Rights demanded by the plaintiff to the defendant. Legal sanctions related to the consideration of judges in Decision No. 1306/K / Pdt.Sus-PHI / 2017, which states that it punishes the defendant to pay severance pay to the plaintiffs in the amount of Rp29, 235, 300.00 (twenty-nine million two hundred thirty-five thousand three hundred rupiah), as a fulfillment of the plaintiff's Rights demanded by the plaintiff to the defendant